Learning the art of electronics a hands-on lab course - Hayes, Thomas C.; Horowitz, Paul 1942- (Cambridge Cambridge University Press, 2016)
"This introduction to circuit design is unusual in several respects. First, it offers not just explanations, but a full course. Each of the twenty-five sessions begins with a discussion of a particular sort of circuit followed by the chance to try it out and see how it actually behaves. Accordingly, students understand the circuit's operation in a way that is deeper and much more satisfying than the manipulation of formulas. Second, it describes circuits that more traditional engineering introductions would postpone: on the third day, we build a radio receiver; on the fifth day, we build an operational amplifier from an array of transistors. The digital half of the course centers on applying microcontrollers, but gives exposure to Verilog, a powerful Hardware Description Language. Third, it proceeds at a rapid pace but requires no prior knowledge of electronics. Students gain intuitive understanding through immersion in good circuit design"--Publisher's website.
Analog: passive devices -- Analog: discrete transistors -- Analog: operational amplifiers and their applications -- Digital: gates, flip-flops, counters, PLD, memory -- Digital: analog-digital, PLL, digital project lab -- Microcontrollers.
Includes bibliographical references and index.
Keywords: Electronic circuits -- Textbooks; Electronic circuits -- Laboratory manuals